Domestic violence in Indian women: lessons from nearly 20 years of surveillance - Rakhi Dandona; Aradhita Gupta; Sibin George; Somy Kishan; G. Anil Kumar (BMC, 2022)
Abstract Background Prevalence of self-reported domestic violence against women in India is high. This paper investigates the national and sub-national trends in domestic violence in India to prioritise prevention activities and to highlight the limitations to data quality for surveillance in India. Methods Data were extracted from annual reports of National Crimes Record Bureau (NCRB) under four domestic violence crime-headings-cruelty by husband or his relatives, dowry death, abetment to suicide, and protection of women against domestic violence act. Rate for each crime is reported per 100,000 women aged 15-49 years, for India and its states from 2001 to 2018. Data on persons arrested and legal status of the cases were extracted. Results Rate of reported cases of cruelty by husband or relatives in India was 28.3 (95% CI 28.1-28.5) in 2018, an increase of 53% from 2001. State-level variations in this rate ranged from 0.5 (95% CI  − 0.05 to 1.5) to 113.7 (95% CI 111.6-115.8) in 2018. Rate of reported dowry deaths and abetment to suicide was 2.0 (95% CI 2.0-2.0) and 1.4 (95% CI 1.4-1.4) in 2018 for India, respectively. Overall, a few states accounted for the temporal variation in these rates, with the reporting stagnant in most states over these years. The NCRB reporting system resulted in underreporting for certain crime-headings. The mean number of people arrested for these crimes had decreased over the period. Only 6.8% of the cases completed trials, with offenders convicted only in 15.5% cases in 2018. The NCRB data are available in heavily tabulated format with limited usage for intervention planning. The non-availability of individual level data in public domain limits exploration of patterns in domestic violence that could better inform policy actions to address domestic violence. Conclusions Urgent actions are needed to improve the robustness of NCRB data and the range of information available on domestic violence cases to utilise these data to effectively address domestic violence against women in India.